2004
DOI: 10.1016/j.mod.2004.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of globin genes of the medaka Oryzias latipes (Euteleostei; Beloniformes; Oryziinae)

Abstract: Recently we cloned two globin gene clusters from the genome of medaka (Oryzias latipes): one designated the embryonic globin gene cluster (E1; (5')alpha0(3')-(3')beta1(5')-(5')alpha1(3')-(5')beta2(3')-(5')alpha2(3')-(3')alpha3(5')-(5')beta3(3')-(3')beta4(5')-(5')alpha4(3')-(3')psialpha(5')-(5')psibeta(3')) and the other the adult globin gene cluster (A1; (3')ad.alpha1(5')-(5')ad.beta1(3')-(3')ad.alpha2(5')). The E1 and A1 clusters map to linkage groups 8 and 19, respectively. The genes beta1/alpha1, alpha3/bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 56 publications
10
35
0
Order By: Relevance
“…In the trees, Antarctic globins form two distinct compact groups, corresponding to major and minor Hbs (33), in agreement with Ref. 59. In contrast, the gadid globins occupy dispersed positions.…”
Section: Zoarcoid Perciformssupporting
confidence: 87%
“…In the trees, Antarctic globins form two distinct compact groups, corresponding to major and minor Hbs (33), in agreement with Ref. 59. In contrast, the gadid globins occupy dispersed positions.…”
Section: Zoarcoid Perciformssupporting
confidence: 87%
“…The obtained topology is in general agreement with the hypothesis of four groups of globins, namely 'Embryonic or Minor Hb Group', 'Notothenioid Major Adult Hb Group', 'Anodic Adult Hb Group' and 'Cathodic Adult Hb Group' (36). The position of the C. gobio and P. urvillii globins is in agreement with phylogenetic evidence from nuclear and mitochondrial genes, according to which C. gobio was the first species to diverge from notothenioids, before P. urvillii [reviewed in (27)].…”
Section: The Molecular Evolution Of Polar Fish Hbsupporting
confidence: 88%
“…Five pairs of the α-and β-globin genes were found to be organized in a head-to-head orientation. We named the paired globin genes based on the head-to-head orientation because in the phylogenic analysis, we found that the gene pair seemed to have coevolved (Maruyama et al 2004b). …”
Section: Communicated By Matthias Hammerschmidtmentioning
confidence: 99%
“…In the previous phylogenetic analysis, we showed that teleost globin genes could be classified into four groups, group I (embryonic Hb), group II (notothenioid major adult Hb), group III (anodic adult Hb), and group IV (cathodic adult Hb) (Maruyama et al 2004b). Group I Hb is embryonic and has a high oxygen affinity and no or little Bohr effect; group II Hb is found mainly in adult Antarctic fish; group III Hb is generally used in adult fishes such as carp, rainbow trout, zebrafish, and yellowtail; and group IV Hb has a low oxygen affinity, high Bohr effect, and Root effect and is found in fishes, such as eel, rainbow trout, and salmon.…”
Section: Communicated By Matthias Hammerschmidtmentioning
confidence: 99%
See 1 more Smart Citation